Upaya Meningkatkan Motivasi Belajar Anak Usia 4-5 Tahun melalui Metode Bernyanyi di TK Al Hidayah Rambipuji Tahun Ajaran 2024 - Anggraeni, Fitria Merie; Ali, A. Zulkarnain; Wijaya, Pipit Rika (Universitas Nusantara PGRI Kediri, 2024)
An important dynamic component in the learning process is motivation. Lack of motivation causes students to underachieve. One of the learning motivations is through singing, an alternative method often used by teachers in the teaching and learning process. Singing is indeed an effective method to increase learning motivation, especially in early childhood. This study was conducted on 22 students with observation and interview data. The results of the study were that children easily feel bored and fed up during learning hours in children aged 4-5 years with a total of 22 students in group B. In class B, there were children who felt bored and fed up so that to help the learning process through the singing method. The results of the pre-cycle observation that the assessment indicator had not developed (BB) reached 95%, there were many students who were not used to the learning process so that it was not fun, making students feel bored and fed up and the assessment indicator began to develop (MB) reaching 5%. Furthermore, 95% were included in the BSB category and 5% were included in the BSH category. This success is due to the fact that children feel happy with learning activities using the singing method and that the variety of songs that are done every day prevents them from getting bored and the results of the actions taken in two locations show that the singing method helps Al Hidayah Rambipuji Kindergarten students learn better.